Immunoproteasomes Down-Regulate Presentation of a Subdominant T Cell Epitope from Lymphocytic Choriomeningitis Virus - Basler, Michael; Youhnovski, Nikolay; Broek, Maries van den; Przybylski, Michael; Groettrup, Marcus (My University, 2004)
The cytotoxic T cell response to pathogens is usually directed against a few immunodominant epitopes, while other potential epitopes are either subdominant or not used at all. In C57BL/6 mice, the acute cytotoxic T cell response against lymphocytic choriomeningitis virus is directed against immunodominant epitopes derived from the glycoprotein (gp33-41) and the nucleoprotein (NP396-404), while the gp276-286 epitope remains subdominant. Despite extensive investigations, the reason for this hierarchy between epitopes is not clear. In this study, we show that the treatment of cells with IFN-gamma enhanced the presentation of gp33-41, whereas presentation of the gp276-286 epitope from the same glycoprotein was markedly reduced. Because proteasomes are crucially involved in epitope generation and because IFN-gamma treatment in vitro and lymphocytic choriomeningitis virus infection in vivo lead to a gradual replacement of constitutive proteasomes by immunoproteasomes, we investigated the role of proteasome composition on epitope hierarchy. Overexpression of the active site subunits of immunoproteasomes LMP2, LMP7, and MECL-1 as well as overexpression of LMP2 alone suppressed the presentation of the gp276-286 epitope. The ability to generate gp276-286-specific CTLs was enhanced in LMP2- and LMP7-deficient mice, and macrophages from these mice showed an elevated presentation of this epitope. In vitro digests demonstrated that fragmentation by immunoproteasomes, but not constitutive proteasomes led to a preferential destruction of the gp276 epitope. Taken together, we show that LMP2 and LMP7 can at least in part determine subdominance and shape the epitope hierarchy of CTL responses in vivo.
Keywords: 570